Kaempferia galanga (L.): An Updated Overview of In Vitro and In Vivo Antioxidant Properties - Riastri, Anami (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2024)
Kaempferia galanga L. (K. galanga) locally called aromatic ginger or “kencur